Virtual Layer: Pepper Ghost Illusion and Digital Projection to Reinforce Place Meaning - Lovendianto, Jeremy; Samodra, FX Teddy Badai; Ekasiwi, Sri Nastiti Nugrahani (Universitas Muhammadiyah Surakarta, 2026)
Placemaking transforms space into place by arranging form, activity, and meaning aspects. In a historical urban village context, the physical forms of historical objects are often altered due to space scarcity and growing needs. It could weaken the historical meaning of the place. Digital technologies could represent the lost historical forms or activities as digital placemaking strategies. Combining the Pepper Ghost illusion technique and digital projection produces a virtual layer to represent past events superimposed onto the site's surroundings to strengthen the place's meaning. It provides a practical digital placemaking strategy for urban village communities. This study aims to evaluate the design prototype of the virtual layer strategy by identifying factors that affect design performance and proposing design recommendations. This study was conducted by experiment and prototype testing. Testing with participants involved semi-structured interviews for data collection and content analysis to identify the factors. This study also provides schematic design implementation in Kampung Kungfu Kapasan, Surabaya. The results recommend designing the screen on a human scale, balancing environmental brightness for content clarity and visual comfort, as well as integrating installation design and surrounding elements. The overlapping strategy of past and present conditions forms a virtual layer as a layered enclosure. It affects how users perceive the surrounding environment, thereby shaping their perception of the place's meaning.